Combination use of tolfenamic acid with curcumin improves anti‐inflammatory activity and reduces toxicity in mice. Issue 6 (13th April 2020) - Zhou, Wei; Liu, Qifa; Zang, Xiaohao; Hu, Mengmeng; Yue, Yuan; Wang, Yuchu; Lv, Chunyan; Du, Zhiyun
Abstract: Long‐term use of tolfenamic acid inevitably causes side effects, including gastric ulcer and hepatotoxicity. Curcumin is generally recognized to be anti‐inflammatory, hepatoprotective, and gastroprotective. Herein, we investigated the combinational effects of tolfenamic acid and curcumin and possible mechanism in a TPA‐induced inflammation mouse model. Combinational use of tolfenamic acid (100 mg/kg) and curcumin (100 mg/kg) by oral administration reduced dermal inflammation represented by ear edema and lymphocytic infiltration. Moreover, curcumin dispersed in polyvinyl pyrrolidone showed stronger synergistic effect. The beneficial effect of the coadministration was also reproduced in PKC/Akt/IKK/NF‐κB signaling pathways. Notably, hepatoprotective and gastroprotective effect was exhibited by the reverse of body weight loss and NF‐κB downregulation in the liver, and by increased Spleen Index of mice. These results suggested combination administration of tolfenamic acid with curcumin enhances anti‐inflammatory efficacy and reduces hepatic/gastric toxicity, which indicates dietary uptake of curcumin may facilitate the function of tolfenamic acid. Practical applications: Curcumin, a representative polyphenolic compound, is one of the main constituents of dietary spice turmeric which has been widely consumed throughout the world, especially in Asia. The beneficial aspect of combination use of curcumin in enhancing anti‐inflammatory effect and reducing hepatic/gastric toxicity of NSAID drug tolfenamic acid in mice has been explored. It might be anticipated as a potential naturally derived bioactive constituent in functional food and pharmaceutical applications. Abstract : Curcumin, a representative polyphenolic compound, is one of the main constituents of dietary spice turmeric which has been widely consumed throughout the world, especially in Asia. The beneficial aspect of combination use of curcumin in enhancing anti‐inflammatory effect and reducing hepatic/gastric toxicity of NSAID drug tolfenamic acid in mice has been explored. It might be anticipated as a potential naturally‐derived bioactive constituent in functional food and pharmaceutical applications.